Herpes Simplex Virus 1-Induced Blood-Brain Barrier Damage Involves Apoptosis Associated With GM130-Mediated Golgi Stress - He, Qiang; Liu, Hui; Huang, Chuxin; Wang, Renchun; Luo, Minhua; Lu, Wei (Frontiers in Molecular Neuroscience, 2020)
Herpes simplex encephalitis caused by herpes simplex virus 1 (HSV-1) infection can lead to a high mortality rate and severe neurological sequelae. The destruction of the blood-brain barrier (BBB) is an important pathological mechanism for the development of herpes simplex encephalitis. However, the specific mechanism underlying the BBB destruction remains unclear. Our previous study found that the Golgi apparatus plays a crucial role in maintaining the integrity of the BBB. Therefore, this present study aimed to investigate the role of the Golgi apparatus in the destruction of the BBB and its underlying mechanisms. Mouse brain endothelial cells (Bend.3) were cultured to establish a BBB model in vitro, and then infected with HSV-1. The results showed that HSV-1 infection caused downregulation of the Golgi-associated protein GM130, accompanied by Golgi fragmentation, cell apoptosis, and downregulation of tight junction proteins occludin and claudin 5. Knockdown of GM130 with small interfering RNA in uninfected Bend.3 cells triggered Golgi fragmentation, apoptosis, and downregulation of occludin and claudin 5. However, overexpression of GM130 in HSV-1 infected Bend.3 cells by transient transfection partially attenuated the aforementioned damage caused by HSV-1 infection. When the pan-caspase inhibitor Z-VAD-fmk was used after HSV-1 infection to inhibit apoptosis, the protein levels of GM130, occludin and claudin 5 were partially restored. Taken together, these observations indicate that HSV-1 infection of Bend.3 cells triggers a GM130-mediated Golgi stress response that is involved in apoptosis, which in turn results in downregulation of occludin and claudin 5 protein levels. Meanwhile, GM130 downregulation is partially due to apoptosis triggered by HSV-1 infection. Our findings reveal an association between the Golgi apparatus and the BBB during HSV-1 infection and identify potentially novel targets for protecting the BBB and therapeutic approaches for patients with herpes simplex encephalitis.